The heiress bride - Hunter, Madeline (Hunter, Madeline. Duke's heiress series, 2023)
Now the new Duke of Hollinburgh, Nicholas Radnor has two duties to fulfill: locate the mysterious woman mentioned in his late uncle's will and acquire a suitable bride. When bedazzling, unconventional Iris Barrington shows up at the estate, Nicholas believes he may have found the missing beneficiary--unless she is a charlatan, or worse. But as for his second duty--he is finding it difficult to think of any other woman while tantalizing thoughts of Iris occupy his mind. He agrees to fulfill the late duke's promise to her, even as he grows suspicious of both her motives and the danger that seems to surround her. All of which keeps her temptingly close at hand...Iris will do anything to restore honor to her beloved grandfather's name. Even tangle with the likes of Nicholas, a man whose formidable intellect and good looks lure her like no other. But all her years on the continent have not prepared her for the sensual onslaught she discovers in his embrace--or the devastation of almost losing him to malicious intentions. Now Iris's desire to unearth the scandal behind the dukedom burns ever brighter: for doing so might also protect the man who has stolen her heart . . .--